Utility of Immature Granulocyte Percentage in Pediatric Appendicitis - Mathews, Eleanor K. (J Surg Res, 2014)
BACKGROUND: Acute appendicitis is the most common cause of abdominal surgery in children. Adjuncts are utilized to help clinicians predict acute or perforated appendicitis, which may affect treatment decisions. Automated hematologic analyzers can perform more accurate automated differentials including immature granulocyte percentages (IG%). Elevated IG% has demonstrated improved accuracy for predicting sepsis in the neonatal population than traditional immature to total neutrophil count (I/T) ratios. We intended to assess the additional discriminatory ability of IG% to traditionally assessed parameters in the differentiation between acute and perforated appendicitis. MATERIALS AND METHODS: We identified all patients with appendicitis from July 2012 to June 2013 by ICD-9 code. Charts were reviewed for relevant demographic, clinical, and outcome data, which were compared between acute and perforated appendicitis groups using Fischer’s exact and t-test for categorical and continuous variables, respectively. We utilized an adjusted logistic regression model utilizing clinical lab values to predict the odds of perforated appendicitis. RESULTS: 251 patients were included in the analysis. Those with perforated appendicitis had a higher white blood cell (WBC) count (p=0.0063), C-reactive protein (CRP) (p<0.0001), and IG% (p=0.0299). In the adjusted model, only elevated CRP (OR 3.46, 95% CI 1.40-8.54) and presence of left shift (OR 2.66, 95% CI 1.09-6.46) were significant predictors of perforated appendicitis. The c-statistic of the final model was 0.70, suggesting fair discriminatory ability in predicting perforated appendicitis. CONCLUSIONS: IG% did not provide any additional benefit to elevated CRP and presence of left shift in the differentiation between acute and perforated appendicitis.